METODE PENGUKURAN KINERJA DENGAN BALANCED SCORECARD: ALTERNATIF PENGUKURAN KINERJA PADA DINAS PENDIDIKAN DASAR KABUPATEN BANTUL - TARUNO, AGUS ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to provide an alternative method of measuring performance in achieving the vision and mission of the Office of Basic Education District Bantul and provide performance measurement approach Balanced Scorecard (BSC) in order to improve the quality of public services sustainable. This study uses the BSC approach as an alternative measurement system at the Office of Basic Education District Bantul conducted with the following stages: a) an analysis of the performance measurement system that runs, b) analysis of the vision and mission of the Office of Basic Education District Bantul to determine the strategic objectives to be achieved in BSC perspectives, c) designing performance measurement system at the Office of Basic Education District Bantul in BSC perspective that outlines the strategic goals to be achieved specifically, the translation of strategic targets, measured in two types of indicators, namely indicators lag and lead indicators, with targets are about to be realized, d) create a cause-effect relationship between strategic objectives in a strategy map in order to realize the strategic themes. In this case the results of interviews with stakeholders, observation and inspection of documents, as well as provisions in the regulations to be considered in designing a performance measurement system to the BSC concept. The research concludes that the application of the BSC concept as an alternative measurement system at the Office of Basic Education District Bantul is feasible because through clearly defined strategy map plot strategy in achieving the organization's vision and mission as a whole, both financial and non-financial aspects and can be useful for improve the quality of education in the future.